ANALYSIS EXECUTION PERIOD RIGHT DEPENDENTS DURING THE INSOLVENCY PERIOD FOR CREDITORS SEPARATIST - Gustaf Hutabarat, Andy; Sunarmi, Sunarmi; Robert, Robert (NOMOI Law Review, 2025)
Term time execution object right liability regulated in Article 55 paragraph (1) of Law No. 37 of 2004 concerning Bankruptcy and Postponement Obligation Debt Payment . Execution right the responsibility is given term 2 months time after commencement of insolvency as in Article 59 paragraph (1) of Law no. 37 of 2004, term time execution does not provide protection to creditors separatist in carry out his rights , so that creditors separatist can experience loss . This study uses method study legal normative referring to norms law with study library , this research is of a descriptive and method descriptive data analysis qualitative . Research Results find If term the time stipulated in Article 59 paragraph (1) of Law No. 37 of 2004 does not provide protection and justice for creditors separatists , this is supported by auction data in period 2019-2023 period owned by KPKNL Medan and creditor data separatist based on this data, creditors separatist need time up to 3 months up to 4 months to implement execution auction guarantee right liability , because there is requirements administrative as well as procedure bureaucracy that must be passed by creditors separatist.